Escape room game for post-stroke cognitive rehabilitation - Ngik, Wendy Jia Wen (2015)
Studies have shown that post-stroke rehabilitation have the highest chance of recovery and reducing rehospitalisation within the first three months. Rehabilitation is aimed to help stroke survivors to relearn the skills that are lost when the stroke hits them, such as the coordination of the hand movement to perform certain tasks. However, patients always find it boring to perform the repetitive task in the rehabilitation training. Thus, the concept of an escape room game is born whereby the user will have to perform repetitive actions in the game. This is to help the user to perform more repetitive tasks unknowingly while having fun, thus they will not be reluctant to do it. This project focuses on the game development of 4 mini games in a Unity3D desktop application. The four mini games are Sandwich Towers of Hanoi, Fridge Entangled Games, Bathroom Sequence, and Recall Phone Number. The mini games will help the players to train their cognitive skills while doing repetitive movements. There are different cognitive domains, discussed in Chapter 2.2 about cognition which have been considered while choosing the game. Currently the game can only handle mouse controls, but the controls of Kinect and Leap Motion combined is considered into account in the development process. Thus, the graphics of the game may not be as aesthetically pleasing. However, the aesthetics issue can be rectified in the future improvement.